2006
DOI: 10.1063/1.2360176
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of solubility limits of transition metals (Co, Mn, Fe, and Ni) in ZnO nanoparticles

Abstract: X-ray diffraction studies on bulk amount of chemically prepared nanocrystalline powder of Zn1−xTMxO (TM=Co, Mn, Fe, and Ni) show that the evolution of secondary phases (Co3O4, Mn3O4, Fe3O4, or NiO) along with the single phase Zn1−xTMxO strongly depend on growth temperature and doping concentration. The highest solubility limits of Co, Mn, Fe, and Ni in ZnO are 30%, 30%, 20%, and 3% (atomic weight), respectively. The magnetization measurement shows that the secondary phase formation reduces the magnetization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 23 publications
5
85
0
1
Order By: Relevance
“…Similar results were obtained by Mote et al [5] for Mn doped ZnO samples prepared by sol-gel route and by Xu [6] for Fe doped ZnO. Upon increasing x, doped samples reveal the formation of secondary phase Zinc Iron Oxide [7] of cubic spinal structure due to coexistence of Fe 3+ ions with Fe 2+ ions in our samples. The lattice parameters, calculated, using the d-spacing equation [8], are listed in table1 and found to be a=0.325 nm and c=0.520 nm, which are similar to those of bulk ZnO [9].…”
Section: Resultssupporting
confidence: 78%
“…Similar results were obtained by Mote et al [5] for Mn doped ZnO samples prepared by sol-gel route and by Xu [6] for Fe doped ZnO. Upon increasing x, doped samples reveal the formation of secondary phase Zinc Iron Oxide [7] of cubic spinal structure due to coexistence of Fe 3+ ions with Fe 2+ ions in our samples. The lattice parameters, calculated, using the d-spacing equation [8], are listed in table1 and found to be a=0.325 nm and c=0.520 nm, which are similar to those of bulk ZnO [9].…”
Section: Resultssupporting
confidence: 78%
“…The secondary phase in the present case was identified with Fe 3 O 4 . 49 Transmission electron microscopy reveals that the powder samples are nanocrystalline in nature with a broad size distribution from 2 to 30 nm with an average size of 7 nm. The structural characterizations have been carried out by using a standard x-ray diffractometer ͑Phillips, PW-1729͒ with monochromatic Cu K␣ radiation and by a highresolution transmission electron microscope ͑JEOL, JEM-2010, 200 kV͒.…”
Section: Sample Preparation and Structural Characterizationmentioning
confidence: 99%
“…The calcination temperature was optimized by repeated investigations such that secondary iron oxide phase formation could be avoided. In a previous study, 49 the optimization procedure for preparing single-phase nanocrystalline systems revealed that both the percentage of TM dopant and the calcination temperature are appropriate for avoiding secondary phase formation. The secondary phase in the present case was identified with Fe 3 O 4 .…”
Section: Sample Preparation and Structural Characterizationmentioning
confidence: 99%
“…[ 10 ] On the other hand, ZnO is a structurally stable n-type semiconductor whose electronic conductivity can be easily enhanced by many orders of magnitude by employing very low doping levels (up to 3% atomic weight) [ 11 ] of Ni. ZnObased oxides supply either electrons or holes in different conditions.…”
Section: Introductionmentioning
confidence: 99%